2004
DOI: 10.1055/s-2004-828621
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Management of Leiomyomata

Abstract: Prior to the advent of modern minimally invasive surgery techniques, the primary surgical management of symptomatic leiomyomata for women desiring future fertility or uterine conservation was through laparotomy. Today, many cases of intramural and subserous leiomyomata are managed with laparoscopic myomectomy and selected cases of submucosal leiomyomata are managed with hysteroscopic myomectomy. The management of leiomyomata endoscopically is one of the more challenging procedures in minimally invasive surgery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The study reported mean EBL to be 169 ± 198 ml with average operative times of 230 ± 83 min. [ 8 ] As surgical experience increases the operative times decrease. [ 9 ]…”
Section: Robotic Myomectomymentioning
confidence: 99%
“…The study reported mean EBL to be 169 ± 198 ml with average operative times of 230 ± 83 min. [ 8 ] As surgical experience increases the operative times decrease. [ 9 ]…”
Section: Robotic Myomectomymentioning
confidence: 99%
“…These issues are thought to affect conversion rates to laparotomy and may play a role in cases of uterine rupture. Much of the steadfast adherence to the open approach has been due to the difficulties encountered with conventional laparoscopy and its associated learning curves [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%